Rhomboencephalosynapsis as a cause of severe vetriculomegaly. Report of two cases - Lacunza Paredes, Rommel Omar (2018)
We report two cases of a rare pathology of the fetal cerebellum, rhomboencephalosynapsis, a defect characterized by the partial or complete absence of the cerebellar vermis, which is currently associated with severe ventriculomegaly due to defects in the formation of the cerebral aqueduct. These are the first cases reported in Peru.